MODERATING EFFECT OF FIRM SIZE ON FIRM VALUE WITH INVESTMENT OPPORTUNITY SET AND INTELLECTUAL CAPITAL AS ANTECEDENT VARIABLES - Puspita, Dyah Aruning; Murtiningtyas, Triana; Saradewi, Luh Winda Pramita (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2021)
This study purposes to analysis the influence of relationship between investment opportunity set and intellectual capital toward firm value and use firm size as a moderating variable. The sample involves 50 companies which the requirement in the high profile company category listed on the Indonesia Stock Exchange in 2017-2019. This research uses SEM PLS in testing the hypothesis. The investment opportunity set variable is measured using MB/VE, VAIC is used to assess intellectual capital, Tobin's Q is used to measure company value, and total assets is used to measure firm size. Investment opportunity has an effect on firm value, intellectual capital has an effect on firm value, firm size can moderate the influence of investment opportunity set on firm value, and firm size has no effect on the relationship between intellectual capital and firm value, according to the findings of the study.